The diploma course in geography at the University of Bayreuth with its special emphasis on Spatial Planning: Course content and success rate - Maier, Jörg (Raumforschung und Raumordnung | Spatial Research and Planning, 1999)
Proceeding from an account of the requirements of professional practice, this article describes the organisation and the content of the course in spatial planning and the qualifications which it leads to. This is followed by an analysis of the types of employment in this field which graduates of this course over the last two decades have entered. One finding stands out: whereas graduates in the early days tended to find employment in the public service, more recently the majority of graduates have taken up positions in the private sector.